Honey Bee Genetic Stock Determines Deformed Wing Virus Symptom Severity but not Viral Load or Dissemination Following Pupal Exposure - Penn, Hannah J.; Simone-Finstrom, Michael D.; Chen, Yanping; Healy, Kristen B. (Frontiers in Genetics, 2022)
Honey bees exposed to Varroa mites incur substantial physical damage in addition to potential exposure to vectored viruses such as Deformed wing virus (DWV) that exists as three master variants (DWV-A, DWV-B, and DWV-C) and recombinants. Although mite-resistant bees have been primarily bred to mitigate the impacts of Varroa mites, mite resistance may be associated with increased tolerance or resistance to the vectored viruses. The goal of our study was to determine if five honey bee stocks (Carniolan, Italian, Pol-Line, Russian, and Saskatraz) differ in their resistance or tolerance to DWV based on prior breeding for mite resistance. We injected white-eyed pupae with a sublethal dose (105) of DWV or exposed them to mites then evaluated DWV levels and dissemination as well as morphological symptoms upon adult emergence. While we found no evidence of DWV resistance across stocks (i.e., similar rates of viral replication and dissemination), we observed that some stocks exhibited reduced symptom severity suggestive of differential tolerance. However, DWV tolerance was not consistent across mite-resistant stocks as Russian bees were most tolerant while Pol-Line exhibited the most severe symptoms. DWV variants A and B exhibited differential dissemination patterns that interacted significantly with treatment group but not bee stock. Further, elevated DWV-B levels reduced adult emergence time while both DWV variants were associated with symptom likelihood and severity. These data indicate that the genetic differences underlying bee resistance to Varroa mites are not necessarily correlated with DWV tolerance and may interact differentially with DWV variants, highlighting the need for further work on mechanisms of tolerance and bee stock-specific physiological interactions with pathogen variants.